Optical coherence tomography assessment of macrophages accumulation in non-ST-segment elevation acute coronary syndromes. Issue 11 (November 2020) - Taglieri, Nevio; Ghetti, Gabriele; Bruno, Antonio G.; Marco, Valeria; Reggiani, Maria L. Bacchi; Bonfiglioli, Rachele; Massarelli, Giulia; Gatto, Laura; Bruno, Matteo; Paoletti, Giulia; Fanti, Stefano; Saia, Francesco; et al.
Abstract : Aims: To investigate in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) the prevalence and the features of optical coherence tomography (OCT)-detected macrophages accumulation in culprit plaques as compared with nonculprit plaques (NCP). Methods: The study is a post-hoc analysis of a prospective study aimed at evaluating the relationship between aortic inflammation as assessed by 18 F-fluorodeoxyglucose-PET and features of coronary plaque vulnerability as assessed by OCT. We enrolled 32 patients with first NSTE-ACS who successfully underwent three-vessel OCT. Results: The median age was 65 (54–72) years and 27 patients (84%) were men. Culprit plaques were clinically defined. Overall, the rate of lipid plaques and lipid plaques containing macrophages were 6.4 and 4.2 per patient, respectively. Culprit plaques had a smaller minimal luminal area, a higher extension of lipid component and a thinner fibrous cap than NCPs. Macrophages accumulations were more likely found in culprit plaque (84 vs. 61%, P = 0.015) in which they had also a higher circumferential extension. On univariable analysis, macrophages accumulation extension had a higher association with culprit plaques (odds ratio = 4.42; 95% confidence interval; 2.54–9.15, P < 0.001) than the mere presence of macrophages accumulation (odds ratio = 3.36; 95% confidence interval; 1.30–8.66, P = 0.012). Culprit plaques with thrombus had a lower distance between macrophages accumulation and the luminal surface than culprit plaque with no thrombus (0.06 vs. 0.1 mm; P = 0.04). Conclusion: In patients with NSTE-ACS, macrophages accumulations are more likely present in culprit plaque in which they disclose also a greater extension compared with those observed in NCP. The distance between macrophages accumulation and the luminal surface is lower in thrombotic culprit plaque than that in nonthrombotic culprit plaque. Abstract : Supplemental Digital Content is available in the text